1999
DOI: 10.1093/humrep/14.5.1318
|View full text |Cite
|
Sign up to set email alerts
|

The probability of abnormal preimplantation development can be predicted by a single static observation on pronuclear stage morphology

Abstract: This retrospective study was undertaken to determine whether further developmental progression of two-pronucleated (2PN) zygotes can be predicted by a single, non-invasive examination of pronuclei, with the use of criteria based on the number and distribution of nucleolar precursor bodies in each pronucleus. The normal range of pronuclear variability was defined by analysis of zygotes giving rise to embryos transferred in 100%-implantation cycles (pattern 0). Morphological patterns differing from pattern 0 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
198
2
23

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(231 citation statements)
references
References 36 publications
8
198
2
23
Order By: Relevance
“…An association between embryos' cleavage rate and morphologic characteristics, and their ability to implant has been reported soon after the first live birth using IVF, and development of controlled ovarian hyperstimulation protocols [3][4][5]. Since then, a multitude of morphologic parameters associated with increased viability of pronuclear, cleavage stage, and blastocyst stage embryos were identified, and numerous embryo grading systems have been developed [6][7][8][9][10][11][12]. These strategies based on embryo morphology, combined with improved culture environment, have led to significant improvements in implantation and pregnancy rates [13], and currently constitute the mainstay of embryo assessment in IVF laboratories worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…An association between embryos' cleavage rate and morphologic characteristics, and their ability to implant has been reported soon after the first live birth using IVF, and development of controlled ovarian hyperstimulation protocols [3][4][5]. Since then, a multitude of morphologic parameters associated with increased viability of pronuclear, cleavage stage, and blastocyst stage embryos were identified, and numerous embryo grading systems have been developed [6][7][8][9][10][11][12]. These strategies based on embryo morphology, combined with improved culture environment, have led to significant improvements in implantation and pregnancy rates [13], and currently constitute the mainstay of embryo assessment in IVF laboratories worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…This is usually achieved either by the extended culture of human embryos to the blastocyst stage [5,6] or by the morphological analysis and selection of the highest quality embryos for transfer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, the assessment of zygote quality has been applied [23][24][25][26][27][28][29][30][31][32]. Although these techniques have greatly assisted in achieving an acceptable pregnancy rate with the minimum number of embryos transferred into the uterus, one aspect of these protocols is that non-transferred embryos are discarded or cryopreserved.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive value of the combination of PN and blastocyst morphologies on pregnancy and implantation rates was also evaluated. Embryos were graded and split into three groups, taking into consideration both the PN status, according to Tesarik and Greco [13], and the blastocyst status, according to the Istanbul consensus workshop on embryo assessment [25].…”
Section: Methodsmentioning
confidence: 99%
“…However, several authors have reported different results regarding the prognostic value of each PN feature. Some studies have reported a strong association between the PN orientation [9][10][11] or the number and distribution of NPB [12][13][14][15][16] and the implantation potential; others have suggested that an increased chance of implantation exists when the cytoplasmic halo is present in zygotes [2,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%